Fanocracy : Turning Fans into Customers and Customers into Fans - Arun Kumar, A. (Prabandhan: Indian Journal of Management, 2020)
This is a book review of Fanocracy : Turning fans into Customers and Customers into Fans by David Meerman Scott and Reiko Scott. David Meerman Scott and Reiko Scott have developed a title that draws the reader’s attention from the first page. The impetus of the book is on who are fans, how they convert into customers, and how customers convert into fans of brands. In this book, the authors interviewed young entrepreneurs, owners of veteran businesses, startup founders, non-profits, and companies big and small to pinpoint which practices separate organizations that flourish from those stuck in stagnation and explore the neuroscience of fandom. The book's content shows how customers’ strong emotions are required for converting into buying power towards a brand. Reiko and David have covered the quintessence of how business firms - large and small - can enlarge and arrange the passions of their best patrons. This book also highlights about how the business organizations think on sharing, community, and justice. The book would be useful to marketing strategists all around the globe. It provides insights into binding loyal customers and how customers are converted into fans and fans are converted into customers.